2019
DOI: 10.3390/d11080126
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Reconstruction of the Neotropical Poison Frogs (Dendrobatidae) and Their Conservation

Abstract: The evolutionary history of the Dendrobatidae, the charismatic Neotropical poison frog family, remains in flux, even after a half-century of intensive research. Understanding the evolutionary relationships between dendrobatid genera and the larger-order groups within Dendrobatidae is critical for making accurate assessments of all aspects of their biology and evolution. In this study, we provide the first phylogenomic reconstruction of Dendrobatidae with genome-wide nuclear markers known as ultraconserved elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…Poison frogs (Dendrobatidae; sensu (AmphibiaWeb, 2020); but see also (Grant et al, 2017;Guillory et al, 2019) are a well-studied group of small Neotropical frogs with parental care (Grant et al, 2006;Lötters et al, 2007;Wells, 2007). The challenges of when, where and how to care for offspring require complex spatio-temporal strategies, making poison frogs ideal organisms to study ecological aspects of movement and orientation (Sinsch, 1990;Sinsch, 2010;Brown, Morales & Summers, 2010;Pittman, Osbourn & Semlitsch, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Poison frogs (Dendrobatidae; sensu (AmphibiaWeb, 2020); but see also (Grant et al, 2017;Guillory et al, 2019) are a well-studied group of small Neotropical frogs with parental care (Grant et al, 2006;Lötters et al, 2007;Wells, 2007). The challenges of when, where and how to care for offspring require complex spatio-temporal strategies, making poison frogs ideal organisms to study ecological aspects of movement and orientation (Sinsch, 1990;Sinsch, 2010;Brown, Morales & Summers, 2010;Pittman, Osbourn & Semlitsch, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The poison frog genus Ameerega Bauer, 1986 is an example of an understudied taxon whose systematics are poorly resolved. Consisting of 30 described species (Table 1) in the subfamily Colostethinae (Grant et al, 2017;Guillory et al, 2019), most Ameerega are found in restricted ranges along the eastern versant of the central and northern Andes from Colombia south to Bolivia, reaching their highest diversity in the eastern Andean foothills of central Peru. However, several taxa, such as A. trivittata and A. hahneli, are widespread throughout the Amazon Basin, and one clade (the braccata group) inhabits the dry savannahs from eastern Brazil to Bolivia.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this deep time scale and numerous rapid radiations across the diversity of frog clades, this exceptional diversity has presented a major challenge for research into amphibian evolution and the performance of custom targeted sequence capture remains largely unexplored (but see Hedtke et al 2013;Portik et al 2016;Salamanders: McCartney-Melstad 2016). Several studies have used UCEs (Alexander et al 2017;Pie et al 2018;Streicher et al 2018;Zarza et al 2018;Guillory et al 2019) and others have used AHE markers (Peloso et al 2016;Heinicke et al 2018;Yuan et al 2018), whereas two additional studies created customized probe sets for an African frog clade (Afrobatrachia) and the Asian genus Limnonectes (Portik et al 2016;Reilly et al 2019). Although UCEs have been used in frogs, they are not ideal because they were designed for amniotes, a group which does not contain frogs; therefore, about half the target UCEs are typically captured (~2500/5600 UCEs ;Streicher et al 2018;Guillory et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used UCEs (Alexander et al 2017;Pie et al 2018;Streicher et al 2018;Zarza et al 2018;Guillory et al 2019) and others have used AHE markers (Peloso et al 2016;Heinicke et al 2018;Yuan et al 2018), whereas two additional studies created customized probe sets for an African frog clade (Afrobatrachia) and the Asian genus Limnonectes (Portik et al 2016;Reilly et al 2019). Although UCEs have been used in frogs, they are not ideal because they were designed for amniotes, a group which does not contain frogs; therefore, about half the target UCEs are typically captured (~2500/5600 UCEs ;Streicher et al 2018;Guillory et al 2019). The AHE probe set is advantageous because it produces long exons that can be more predictably modelled.…”
Section: Introductionmentioning
confidence: 99%